Efektivitas Strategi Murder (Mood, Understand, Recall, Digest, Expand, Review) Terhadap Hasil Belajar Matematika Siswa - Iffah Nur Afifah; Sri Satriani; Andi Husniati (Delta: Jurnal Ilmiah Pendidikan Matematika, 2023)
This type of research is pre-experimental with the research design used, namely the One Group Pretest-Posttest Design which involves one class as an experimental class that aims to determine the effectiveness of learning mathematics through the application of the MURDER strategy to class X students of SMAN 7 Wajo. The sample in this study was class X IPA 1 with a total of 36 students. Data collection techniques used to collect data are tests of students' mathematics learning outcomes, student activity observation sheets, and student response questionnaires. The analysis of the research data is descriptive statistical analysis and inferential statistical analysis. The results showed that the effectiveness of learning mathematics through the application of the MURDER strategy to class X students of SMAN 7 Wajo was effectively applied with the following description: (1) The increase in students' mathematics learning outcomes after the application of the MURDER strategy was in the medium category with an average normalized gain value of 0.699. (2) Student activity during the process of learning mathematics through the application of the MURDER strategy is in the active category with an average active student of 82%. (3) Student response to the process of learning mathematics through the application of the MURDER strategy reaches 81%, which is positive.